Child’s lawyer in Ukraine (Law and Safety, 2023)
It has been analyzed the opinions of scholars and lawyers on the definition of the concept of “a child’s lawyer”. The author’s definition on the concept of “child’s lawyer” has been formulated, which should be understood as a person who carries out legal activities on the grounds and in accordance with the procedure provided for by law, and which consists in the independent professional activity of a lawyer in the field of defense, representation and provision of other types of legal assistance to a person under 18 years of age (majority). Taking into account the levels of specialization in the bar, it has been established that the specialization “child’s lawyer” can be both at the corporate level (creation of a structural unit in the system of bar self-government bodies responsible for the protection of children’s rights) and at the professional level (the law provides for the practice of the legal profession individually, through a law firm and a law association, which are also engaged in the protection of children's rights). It has been proved that the branch differentiation of law, based on the theory of differentiation of legal relations, is generally accepted for the specialization of Ukrainian lawyers. It has been proposed to distinguish a child as an individual to whom a child’s lawyer provides legal aid, i.e., as a type of a lawyer’s client. It has been noted that Ukrainian legislation operates with special concepts such as “ensuring the best interests of the child”, “child abuse”, “child in difficult life circumstances”, “child in need of additional protection”, “contact with the child”, which are inherent only in cases involving a child.It has been analyzed the opportunities provided by the Higher School of Advocacy of the National Bar Association of Ukraine for obtaining the specialization of a child lawyer. In order to develop the idea and unite the relevant lawyer community “child lawyer”, lawyers are being certified, a register of child lawyers is being maintained, and specialists are constantly deepening their thematic specialization and providing information and support.It has been analyzed the experience of other countries regarding the use in practice of the concepts of “child’s lawyer” in family courts, “child protection advocacy” and established the requirements for a child’s lawyer.
Keywords: lawyer; advocacy; children’s law; child; child’s lawyer; children’s rights; minors.